Control and Nonlinearity - Coron, Jean-Michel (American Mathematical Society Rhode Island, 2007)
Presents methods to study the controllability and the stabilization of nonlinear control systems in finite and infinite dimensions. The emphasis is on specific phenomena due to nonlinearities. In particular, many examples are given where nonlinearities turn out to be essential to get controllability or stabilization.
Includes Bibliographical References And Index
Keywords: Control Theory; Nonlinear Control Theory